Effect of different load during eccentric training with blood flow restriction on muscle size, strength, and performance: A randomized controlled trial✰ - Biral, Taíse Mendes [UNESP]; Lemos, Leonardo Kesrouani [UNESP]; Cavina, Allysiê Priscilla de Souza [UNESP]; Junior, Eduardo Pizzo [UNESP]; Vendrame, Julia Waszczuk [UNESP]; da Silva, Gabriel Martins [UNESP]; Brandão, Guilherme Henrique da Silva [UNESP]; Pimenta, Gabriella Souza Oliveira Meireles [UNESP]; da Silva, Gabriel Oliveira [UNESP]; Santos, Gabriel Cena [UNESP]; de Oliveira, Enzo Vinícius Corrêa [UNESP]; Vanderlei, Franciele Marques [UNESP] (Elsevier, 2025)
Background/Objective: studies on eccentric training with blood flow restriction (BFR) still has gaps, especially in strength and muscle hypertrophy. Therefore, this study aimed to analyze and compare the effects of six weeks of eccentric training of knee extensors at different load associated or not with BFR on strength, hypertrophy, and performance of knee extensors. Methods: 61 men, healthy and untrained, performed six weeks of quadriceps muscle eccentric training in isokinetic dynamometer were randomized into four groups: high-load eccentric training with BFR (HLET-BFR), low-load eccentric training with BFR (LLET-BFR), high-load eccentric training (HLET) and low-load eccentric training (LLET). The strength, muscle structure and performance outcomes were evaluated at baseline, after 3 and 6 weeks of training. Results: for eccentric peak torque in the first three weeks, HLET was superior to LLET, but similar to LLET-BFR. In the final three weeks, superiority was observed in relation to LLET-BFR; however, there was no difference in relation to HIET-BFR. For the outcomes isometric and concentric peak torque, muscle structure and performance, there were no differences between groups. Conclusion: eccentric training led to strengthening of knee extensors and improved performance, but without altering the muscle structure. LLET-BFR promoted gains similar to HLET in the first three weeks of training.
Keywords: Force; Hypertrophy; Muscle structure; Occlusion vascular; Resistance training